Inside the body : fantastic images from beneath the skin. - Chorlton, Windsor, ....- (London : Cassell Illustrated, 2004)
It's time to see te body as you've never seen it before. Inhoud: Cells Tissues Systems Brain and senses
Keywords: Anatomie; Menselijk lichaam